Workshop, Assessment, and Validity Evidence for Tools Measuring Performance of Knee and Shoulder Arthrocentesis - Jacob Murray; Andrea Ramirez-Gomez; Mike Cahill; Amber Deptola; Colin Diffie; Peter McDonnell; John P. Metzler; Nathan P. Olafsen; Lisa Zickuhr (Association of American Medical Colleges, 2023)
Introduction Musculoskeletal concerns are common, yet residents at our institution lacked arthrocentesis training. We created a workshop to teach residents knee and shoulder arthrocentesis, developed simulated assessment scenarios (SASs) with tools to measure procedural proficiency, and collected validity evidence. Methods A multidisciplinary group conducted a modified Delphi to define content for the workshop, SASs, and assessment tools. We defined minimum thresholds for competence in knee and shoulder arthrocentesis using the modified borderline-group method. We implemented the workshop and SASs in 2020 and 2021 and analyzed assessment tool scoring for statistical reliability and validity. Our program evaluation included SAS performance, participants' survey responses, and change in the number of arthrocenteses performed in the internal medicine (IM) resident primary care clinic. Results Sixty-one residents (53 IM, eight physical medicine and rehabilitation [PM&R]) participated. Fifty-two (85%; 46 IM, six PM&R) completed the evaluation survey. We procured data from 48 knee and 65 shoulder SASs for validity evidence. All arthrocentesis SAS performances met the proficiency standard except one resident's shoulder SAS. Validity evidence revealed strong interrater reliability (α = .82 and .77 for knee and shoulder, respectively) and strong relational validity (p < .001 for both procedures). All participants rated workshop quality and usefulness as good or very good. The number of arthrocenteses performed at our institution's primary care clinic increased. Discussion We created a workshop to teach residents arthrocentesis and assessment tools with strong validity and reliability evidence. The workshop was well regarded by residents, who applied their arthrocentesis skills during patient care.